The biomechanical analysis of the snatch lift in top-class Japanese female weightlifters - Characteristics of a good snatch player from a coach's point of view - Kobatake, N.; Nagao, H.; Miura, T. (Journal of High Performance Sport, 2022)
This study aimed to identify the characteristics of snatch lift in top-class Japanese female weightlifters. The hypothesis was that lifters who are good at the snatch had lower barbell velocity in the 1st pull and longer heel contact time based on their weightlifting coaching points. Female lifters who competed in the 2021 All Japan Women's Weightlifting Championships were included in the study. Lifters who had a small difference in scores between the best attempts in snatch and clean & jerk lifts comprised Group A (good at snatch), while those who had a greater difference in scores comprised Group B (NOT good at snatch). The two-dimensional position coordinates of the barbell of each athlete's best snatch attempt during competition were calculated from video analysis to determine the kinematic variables of the barbell. Heel contact time was also determined from video images and compared between groups. The results supported the hypothesis: athletes in Group A had a significantly smaller mean vertical velocity of the barbell in the 1st pull phase than the athletes in Group B (0.45±0.05[m/s], 0.52±0.05[m/s], p<0.001, d=1.179). However, there were no significant differences in mean vertical velocity of the barbell in the 2nd pull phase or in vertical maximum velocity between groups. Heel contact time was also significantly larger in Group A (0.61±0.04[s], 0.53±0.06[s], p<0.001, d=1.347). Finally, there was a negative relationship between the mean vertical velocity of the barbell during the 1st pull phase of the snatch and the best snatch attempt that standardized body weight (r=-0.287, p<0.05). These results suggest that slow and careful execution of the 1st pull and keeping the feet flat in the snatch positively affect the performance.